Biosynthesis of Octacosamicin A: Uncommon Starter/extender Units and Product Releasing via Intermolecular Amidation - Liao, Yanghui; Wang, Xue‐Jiao; Ma, Guang‐Lei; Candra, Hartono; Qiu En, Sean Lee; Khandelwal, Srashti; Liang, Zhao‐Xun (Chembiochem : a European journal of chemical biology, 2024)
Octacosamicin A is an antifungal metabolite featuring a linear polyene‐polyol chain flanked by N‐hydroxyguanidine and glycine moieties. We report here that sub‐inhibitory concentrations of streptomycin elicited the production of octacosamicin A in Amycolatopsis azurea DSM 43854T. We identified the biosynthetic gene cluster (oca BGC) that encodes a modular polyketide synthase (PKS) system for assembling the polyene‐polyol chain of octacosamicin A. Our analysis suggested that the N‐hydroxyguanidine unit originates from a 4‐guanidinobutyryl‐CoA starter unit, while the PKS incorporates an α‐hydroxyketone moiety using a (2R)‐hydroxymalonyl‐CoA extender unit. The modular PKS system contains a non‐canonical terminal module that lacks thioesterase (TE) and acyl carrier protein (ACP) domains, indicating the biosynthesis is likely to employ an unconventional and cryptic off‐loading mechanism that attaches glycine to the polyene‐polyol chain via an intermolecular amidation reaction. The biosynthesis of octacosamicin A requires uncommon starter and extender units and likely employs an unusual mechanism for product release by catalysing an intermolecular amidation reaction.